Languaging to trigger change: second-order intercultural conversations with urban youth of Maya descent - Sidorova, Ksenia; Peniche Pavía, Francia; Rivero Pérez, Astrid Karina (Journal of Sociocybernetics, 2021)
The paper presents an applied research project that looks into whether the Yucatec Maya language can become an identity factor for the urban youth of Maya descent inhabitants of a marginal urban area in southeastern Mexico, against the entropic tendency towards the Yucatec Maya language loss in the urban environment. Our starting point is Maturana’s idea that through languaging and emotioning human worlds are built and maintained; our lives are intertwined in interactional networks, therefore we only exist as human beings through conversations we hold with other human beings. We go on to explore the types of connection to the Maya culture and language in the case of the young men and women who took part in a workshop “My life and the Maya culture: roots and relations”, and how this connection is constructed through languaging and emotioning whithin their families, personal networks, and the workshop itself. The conversations –that emerge through languaging and emotioning– are seen as potential triggers of changes in representations and attitudes towards the minorized language and culture. We also maintain that for the changes to be sustainable, the rest of the local society, viewed as a cultural multiverse (Krotz, 2004), is to recognize Maya speakers as legitimate others (Maturana & Nisis, 2014), so that the non-Maya groups are also to engage to ensure the structural coupling between the diverse parts that conform the multiverse. Our role as researchers, then, is not that of external observers; we assume our part in the cultural multiverse as participants in its construction who by languaging, emotioning, and subsequent acting, seek to contribute to a broader acceptance and respect towards the minorized language and its speakers.